Uso de visão computacional em dispositivos móveis para auxílio à travessia de pedestres com deficiência visual - Sousa, Kelly Aparecida Oliveira (2013)
This project presents an application that is intended to assist the visually impaired in crossing streets using mobile devices. This work also examined the challenges and some solutions to develop mobile interfaces available that perform image processing for crosswalks and people detection. Further information is given about using the OpenCV Library for the Android platform and the differences in the processing of computer vision algorithms between the mobile and other environments. The results presented demonstrate the feasibility of the project. It is also pointed out the future work required to improve the current system.